China Learns from the Soviet Union, 1949-Present. - Bernstein, Thomas P.; Li, Hua-Yu (Rowman & Littlefield Pub. Group, 2009)
It is well known that the Soviet Union strongly influenced China in the early 1950s, since China committed itself both to the Sino-Soviet alliance and to the Soviet model of building socialism. What is less well known is that Chinese proved receptive notonly to the Soviet economic model but also to the emulation of the Soviet Union in realms such as those of ideology, education, science, and culture. In this book an international group of scholars examines China's acceptance and ultimate rejection of Soviet models and practices in economic, cultural, social, and other realms. The chapters vivi.